2009
DOI: 10.1016/j.neuroscience.2009.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Reduced anticipatory locomotor responses to scheduled meals in ghrelin receptor deficient mice

Abstract: Ghrelin, an orexigenic hormone produced by the stomach, is secreted in anticipation of scheduled meals and in correlation with anticipatory locomotor activity. We hypothesized that ghrelin is directly implicated in stimulating locomotor activity in anticipation of scheduled meals. To test this hypothesis, we observed 24 hr patterns of locomotor activity in mice with targeted mutations of the ghrelin receptor gene (GHSR KO) and wild-type littermates, all given access to food for four hours daily for 14 days. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
172
3
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(196 citation statements)
references
References 38 publications
16
172
3
5
Order By: Relevance
“…Interestingly, GHSR-deficient mice also exhibit diminished behavioral activation and reinforcement responses to cocaine and nicotine (Abizaid et al, 2011;Jerlhag and Engel, 2011), and it has been proposed that ghrelin signaling could induce a form of central sensitization in which animals are more reactive to rewarding stimuli (Wellman et al, 2013). Indeed, it has been shown that GHSR-deficient mice display a reduced anticipatory locomotor response to scheduled meals (Blum et al, 2009). To our knowledge, current results are the first report of the requirement of the ghrelin signaling for HFD escalation in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, GHSR-deficient mice also exhibit diminished behavioral activation and reinforcement responses to cocaine and nicotine (Abizaid et al, 2011;Jerlhag and Engel, 2011), and it has been proposed that ghrelin signaling could induce a form of central sensitization in which animals are more reactive to rewarding stimuli (Wellman et al, 2013). Indeed, it has been shown that GHSR-deficient mice display a reduced anticipatory locomotor response to scheduled meals (Blum et al, 2009). To our knowledge, current results are the first report of the requirement of the ghrelin signaling for HFD escalation in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Animals with limited access to food learn to anticipate food availability by increasing locomotion (food anticipatory activity, FAA) and optimize their consummatory behavior during that period. Ghrelin signaling is critical for FAA and consumption (Blum et al, 2009;Verhagen et al, 2011). When assessed on chow diet, we found that total locomotor activity by AgRP-ablated mice was initially decreased relative to control mice but activity recovered by day 5; when the mice were on HFHS diet, the AgRP-ablated group recovered normal locomotion faster ( Figure 7A).…”
Section: Agrp-ablated Mice Display Impaired Feeding But Abnormal Antimentioning
confidence: 93%
“…There is no doubt that FAA stems from activity within the brain, although the initiation of this activity may arise from peripheral oscillating or stimulating processes (38)(39)(40). All in all, the appearance of c-Fos or PERIOD immunoreactivity in many brain areas after food restriction and the failure to prevent FAA by lesioning different brain areas (13) suggests that the organization of the oscillatory nature of FAA should be within a system of interacting brain structures.…”
Section: Faa Is Lost After Lesion Of the Dmh But Reappears After Amentioning
confidence: 99%